Association between household food insecurity and stunting in children aged 0−59 months: Systematic review and meta‐analysis of cohort studies - Érika S. O. Patriota; Lívia C. S. Abrantes; Ana C. M. G. Figueiredo; Nathalia Pizato; Gabriela Buccini; Vivian S. S. Gonçalves (Wiley, 2024)
Abstract Household food insecurity (HFI) during childhood is associated with poor dietary diversity and malnutrition, placing children's growth at risk. Children with growth disorders, such as stunting, are more likely to have poor cognition and educational performance, lower economic status, and an increased risk of nutrition‐related chronic diseases in adulthood. Our study aimed to systematically review and conduct a meta‐analysis of cohort studies investigating the association between HFI and stunting in children aged 0−59 months. Peer‐reviewed and grey literature were systematically searched in electronic databases with no language or date restrictions. Two reviewers independently assessed the studies for pre‐established eligibility criteria. Data were extracted using a standard protocol. Random‐effects meta‐analysis models were used, and I2 > 40% indicated high heterogeneity across studies. We used the Grading of Recommendations Assessment, Development, and Evaluation system to assess the quality of the evidence. Nine cohort studies comprising 46,300 children were included. Approximately 80% (n = 7) of the studies found a positive association between HFI and stunting. Pooled odds ratio was 1.00 (95% confidence interval [CI]: 0.87−1.14; I2: 76.14%). The pooled hazard ratio between moderate and severe HFI and stunting was 1.02 (95% CI: 0.84−1.22; I2: 85.96%). Due to high heterogeneity, the quality of evidence was very low. Individual studies showed an association between HFI and stunting in children aged 0-59 months; however, this association was not sustained in the pooled analysis, possibly because of high heterogeneity across studies.